English for specific purposes: from origins to contemporary trends - Duzhyk, Nataliia (My University, 2021)
The paper reviews the foundation and formation of ESP. The main concern of the paper is ESP specialists’ activities and finding the ways to enhance their professional expertise. The possibility of employing various methods and approaches while teaching ESP is considered, as well as applying an eclectic approach to teaching.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; teacher competence; computer-based learning; навчання; англійська мова; компетентність викладача; комп’ютерне навчання